2015
DOI: 10.5539/mas.v9n7p1
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Marasmius sp. on Biopulping of Oil Palm Empty Fruit Bunches

Abstract: White rot fungi have an ability to degrade lignin by employing lignin-degrading enzymes i.e Lignin Peroxidase, Manganese Peroxidase and Laccase. Therefore, the fungi can be utilized on the pretreatment of biomass in pulp making (biopulping) and biobleaching. In this study, the pretreatment using White Rot Fungi of Marasmius sp. has been conducted on the the Oil Palm Empty Fruit Bunches (EFBs). Marasmius sp. has been grown on EFBs for 30 days. The results showed that the lignin content could be removed by 35.94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 17 publications
0
4
0
4
Order By: Relevance
“…The surface area was one of the important substrate properties which can improve the fungus growth during SSF [20]. Another research by [21] also reported enhanced growth of Marasmius sp. on chopped EFB in bio pulping pre-treatment using an SSF system.…”
Section: Fungal Culture and Solid-state Fermentation Systemmentioning
confidence: 99%
“…The surface area was one of the important substrate properties which can improve the fungus growth during SSF [20]. Another research by [21] also reported enhanced growth of Marasmius sp. on chopped EFB in bio pulping pre-treatment using an SSF system.…”
Section: Fungal Culture and Solid-state Fermentation Systemmentioning
confidence: 99%
“…For biopulping process, selective lignin degradation is required. Thus, only fungi having high ligninolytic enzyme system, yet remarkably low cellulolytic activity are suitable for biopulping (Risdianto, Sugesty, 2015). After 20 days pretreatment of rice straw, L. lactinea CP9 already colonized the whole material (Fig.…”
Section: Pretreatment Of Rice Traw Of Leiotrametes Lactinea Cp9mentioning
confidence: 99%
“…124 In a previous work using oil palm biomass as the substrate for the pretreatment or not (control) with the fungus T. versicolor, during 1, 2, 3, and 4 weeks, the highest levels of laccase, MnP and LiP activities were respectively 218.66 U L -1 , 162.10 U L -1 and 42.56 U L -1 , while the levels of cellulase and hemicellulase activities were insignificant in all extracts (53.30 and 1.50 U L -1 , respectively). 124 Hand sheet properties were also improved significantly by such fungal treatment, being the the weight, lignin, cellulose and holocellulose losses of respectively 8.45%, 9.35%, 4.58%, and 7.2%. Images from SEM indicated a simultaneous type of decay pattern involving cell wall breakdown combined with lignin modification.…”
Section: Fungal Potential For Biopulping and Biobleachingmentioning
confidence: 99%